Effectiveness of Coordination and Supervision of the Corruption Eradication Commission in Preventing Criminal Acts of Corruption and Misuse of Regional Assets (Research Study on the Deputy for Coordination and Supervision of the Corruption Eradication Commission of the Republic of Indonesia) - Marvelous, Marvelous; Bawono, Bambang Tri (Jurnal Hukum Khaira Ummah, 2025)
The Corruption Eradication Commission has a duty to prevent corruption. One of the deputies that has the duty to prevent corruption is carried out by the Deputy for Coordination and Supervision. Prevention of corruption is very important for the KPK to do by coordinating with other agencies in the regional government. Coordination between law enforcement and the regional government must have a positive impact on reducing the number of corruption cases. The form of implementation is the prevention of corruption against regional assets. Regional assets are in the form of land controlled by third parties. As in the case of the Sorong City Regional Government. That in the case of the former land of the Agriculture Service located on Jalan Jenderal Sudirman (in front of the Sorong City District Court), Melawai Village, Manoi District, Sorong City, West Papua Province, the type of livestock land is 1712 M2 with a Certificate of Use Rights Number 306 dated September 8, 1984 which is controlled by a third party. Therefore, the Sorong City Regional Government coordinated with the Deputy for Coordination and Supervision of the KPK in an effort to regain the rights to the regional government assets. The problem raised in this study is how the implementation of KPK coordination and supervision in preventing criminal acts of corruption in the misuse of regional assets. And how effective is the coordination and supervision of the KPK in preventing criminal acts of corruption in the misuse of regional assets. The research method used in this study is sociological normative legal research. This study uses an effectiveness approach. This study uses primary data and secondary data. The data collection method uses interviews and literature studies with analytical descriptive research specifications and analysis methods using evaluative analysis. The results of the study show that collaboration and coordination between the KPK and the regional government are the keys to success in preventing misuse of regional assets. The role of the Deputy for Coordination and Supervision of the KPK is very central in preventing criminal acts of corruption. In preventing criminal acts of corruption, the Deputy for Coordination and Supervision coordinates with the Regional Government, Prosecutor's Office and Police to save regional assets. Coordination between law enforcers is a crucial element in realizing effective, efficient and equitable legal certainty. Obstacles affecting the coordination and supervision of the KPK in preventing misuse of regional assets include the lack of integration of regional asset data, weak commitment of regional governments, overlapping authority between institutions, and limited human resources and technology. In addition, there is still a bureaucratic culture that is less responsive to supervision and low anti-corruption awareness at the regional level.